Social work theory in practice - Heslop, Philip; Meredith, Cathryn (London : SAGE Publications Ltd, 2021)
A step-by-step guide to the underpinning theoretical knowledge in social work helping your students to confidently apply theory in practice. {u2003}-{u2003}Exercises will help them get to grips with the essentials and reflect on learning. {u2003}-{u2003}Case studies from eight fictional social workers located in a busy local authority office will allow them to explore a range of different practice experience, theoretical perspectives and approaches to understanding situations and identifying possible courses of action. {u2003}-{u2003}The authors' own experiences will show the importance of reflection, supervision and continual learning to help them prepare for the reality of practice.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Social service -- Vocational guidance